Pelatihan uji kompetensi keahlian siswa sekolah kejuruan menggunakan metode Participatory Learning and Action (PLA) - Putra, Yupi Kuspandi; Sadali, Muhamad; Fathurrahman, Fathurrahman; Mahpuz, Mahpuz (Universitas Hamzanwadi, 2020)
National examination for skills competency at vocational high schools is held annually by the central government. The implementation of the national examination is one of the determinants of graduation apart. A national examination is also used for three other things: mapping, selecting to a higher level, and providing assistance or affirmation to the regions. Local governments can also use the national examination to mapping the achievements' standards for students, academic units, and regions. This community service aims to help students increase students' readiness and expertise in solving the national exam for competency skills in the multimedia field. This activity's target is the XII grade students of SMK NW Wanasaba, the main partners. This activity's target and output is the development of skills to work on skills competency National Examination questions, which are skills. The method is Participatory Learning and Action (PLA). This activity was providing practical knowledge and skills to students of SMK NW Wanasaba. This expertise competency training, especially in the multimedia field, can help students prepare for expertise competency exams to get maximum results and improve student competence